O CANGAÇO DE GLAUBER ROCHA: Uma análise sobre o banditismo social em Deus e o diabo na terra do sol, sob a ótica do humanismo - PINTO, Adriano Versiani (2024)
In the recent history of our country, we have experienced moments characterized, in part, by negative discourses on human rights, marked by a lot of sectarianism, and intolerance towards differences, which is why it is necessary for topics such as humanism to be debated and analyzed. Within this scope, I chose to reanalyze social banditry with a humanist focus. Glauber Rocha, one of the most important Brazilian filmmakers of the 20th century and one of the main exponents of Cinema Novo, emphasized the phenomenon of cangaço as an expression of social banditry. In his film "God and the Devil in the Land of the Sun", he uses epic and realistic elements to portray the struggle of country people against social oppression and economic inequality in the northeastern hinterland of Brazil, here favoring a humanistic approach to the theme. From this perspective, his vision of humanism can also be found, directly or indirectly, in all his other films, in addition to signing documents, letters and even a novel, which justifies the choice of his work in this research. Thus, the present dissertation aimed to carry out a reading of cangaço from a humanist perspective, based on the work Glauber Rocha. To this end, as specific objectives, we analyzed how these relationships are processed in the film God and the Devil in the Land of the Sun, and also how the intermediation between humanism and criminology takes place in understanding the cangaço event, concluding that this historical and social concept requires of a criminological analysis, especially cultural criminology. As a methodological route, I opted for Paul Ricoeur's proposal on the construction of mimesis, used in the work Time and Narrative, so that the work is divided into mimesis 1, 2 and 3. From this perspective, and for the expected objectives, the film analysis, in which the identification and interpretation of key scenes, dialogues, and the construction of characters related to cangaço and social banditry were carried out. Film analysis tools were used, such as cinema semiology, anchored in the thinking of theorists such as Marc Ferro, Luís Costa Lima and Ismail Xavier, who helped in the interpretation of symbols and metaphors present in the work.